LANGUAGE LEARNING CULTURALLY AND THE ROLE OF LITERATURE IN TEACHING PROCESS.: LANGUAGE LEARNING CULTURALLY AND THE ROLE OF LITERATURE IN TEACHING PROCESS. - Karimov, Davron (Maktabgacha taʼlim jurnali, 2021)
The topic identifies about the aspects on the language learning and the importance of the culture communication accompanied by literature through teaching stages. The aim is to investigate the effectiveness of incorporating culturally-loaded materials like literature in EFL classes. In EFL teaching, literature is utilized as a pedagogic tool to produce more speech materials that they consider really situational and very communicative. It also explores the suitable activities and methods to teach literature in order that it can help teachers of English elevate the quality in their teaching along with make use of these methods in teaching language skills: reading, writing, listening, speaking as well as language areas, namely vocabulary, grammar and pronunciation. Thus, we try to show a number of the valuable ways of skills so as to teach languages and demonstrate learning the language through the literature and appropriate solutions of the studying the literary texts.